2011
DOI: 10.4028/www.scientific.net/amr.311-313.906
|View full text |Cite
|
Sign up to set email alerts
|

Stress Field Numerical Simulation of the Inclusions in Large Rudder Arm Steel Casting

Abstract: The influences of non-metallic inclusions on the quality and properties of the steel not only depended on the quantity of inclusions, but also on the type、shape、size、deformation behavior and distribution condition. By means of ANSYS finite element analysis software, the stress field distribution in the inclusions and the matrix around the inclusions are analyzed under the condition of different kinds of types、shapes、distributions with changeable load in heavy rudder arm steel castings, then micromechanics beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
1
5
0
2
Order By: Relevance
“…In the fiber models with circular cross-section, a gradual variation of stresses was observed throughout the fiber-matrix interface. A similar stress increase was observed in Xie et al 18 as well where much higher interface stresses were observed in polygonal-shaped inclusions in the matrix compared to the circular ones.…”
Section: Steelsupporting
confidence: 86%
See 1 more Smart Citation
“…In the fiber models with circular cross-section, a gradual variation of stresses was observed throughout the fiber-matrix interface. A similar stress increase was observed in Xie et al 18 as well where much higher interface stresses were observed in polygonal-shaped inclusions in the matrix compared to the circular ones.…”
Section: Steelsupporting
confidence: 86%
“…It is known that polygon corners can generate additional stress concentrations. 18 The objective of this study was to investigate stress concentrations in unidirectional steel fiber composites subjected to transverse tensile loading and to compare them to the ones in carbon and glass fiber composites. The stresses in the matrix and at the fiber-matrix interface were analyzed for an isolated single fiber, and for multiple fibers in hexagonal and random fiber packings.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is worth noting that the effect of inclusions on material fatigue behaviour also varies with the depth. Numerous simulations as reported in Moghaddam et al have demonstrated that when inclusion appears in the position of 0.5 b beneath the contact surface ( b refers to the half Hertzian contact width), material failure occurred most probably. Figure shows the implementation of the inclusion into the generated microstructure of the RVE domain.…”
Section: Methodsmentioning
confidence: 99%
“…There are several studies about steel cleanliness and control of nonmetallic inclusions to minimize the negative influence of critical inclusions and improve the fatigue strength [13,14]. In addition, the study of non-metallic inclusions, in particular with respect to their type, area, shape and position, is of high interest in order to predict the fatigue strengths of engineering steels and allow for safe design [1,[15][16][17][18][19]. Besides approaches to enhance the purity of steels and minimizing critical inclusion formation during steel production, a thermomechanical treatment (TMT) in the temperature range of maximum dynamic strain aging (DSA) is another approach to increase the fatigue strength of steels by strengthening the microstructure around the inclusions after the steel production [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The shape, size and inclusion depth of crackinitiating non-metallic inclusions were investigated and analyzed by other researchers. However, these investigations are mostly simulation-based [15,23]. There are experimental investigations reporting no correlation between the areas of critical non-metallic inclusions or inclusion depth and lifetime (N f ) [9,24,25].…”
Section: Introductionmentioning
confidence: 99%